Spectrophotometric sensor system based on a liquid waveguide capillary cell for the determination of titanium: Application to natural waters, sunscreens and a lake sediment - Páscoa, Ricardo N. M. J. (2012)
An analytical procedure for the spectrophotometric determination of titanium at trace levels was developed. The procedure involves the use of a multipumping flow system (MPFS) coupled with a liquid waveguide capillary cell (LWCC) with 1.0 m path length, 550 mm i.d. and 250 mL internal volume, which enabled to enhance the sensitivity of the determination and thus avoid complex and timeconsuming preconcentration steps. The determination is based on the colorimetric reaction of titanium with chromotropic acid. The limit of detection (3 ) was 0.4 mg/L and a linear response up to 100 mg/L with a sample throughput of 46 h−1, and a low reagent consumption/effluent production was achieved. The developed procedure was applied to natural waters, sunscreen formulations and one certified lake sediment sample.